Depressive Disorder in Thyroid Cancer Patients after Thyroidectomy: A Longitudinal Follow-up Study Using a National Cohort. (February 2019) - Choi, Hyo Geun; Park, Bumjung; Ji, Yong Bae; Tae, Kyung; Song, Chang Myeon
Objective: The present study compared the frequency of depressive disorder in patients with thyroid cancer who had undergone thyroidectomy with the frequency in control individuals. Study Design: Retrospective population-based cohort study. Setting: This study used data from the Korean Health Insurance Review and Assessment Service–National Sample Cohort. Subject and Methods: A total of 3609 participants with thyroid cancer who had undergone thyroidectomy between 2003 and 2011 were enrolled in this study and matched 1:4 with 14, 436 control participants by age, sex, income, and region of residence. The cumulative incidence of postoperative depressive disorder was evaluated over a period of 10 years after the thyroidectomies and compared with the incidence in controls. Depressive disorder was diagnosed by a psychiatrist. Results: The incidence of depressive disorder was significantly higher in the thyroid cancer with thyroidectomy group than in the controls up to postoperative year 1. A subgroup analysis showed the same higher incidence of depressive disorder in the thyroid cancer group than controls for up to 1 year after operations in young adult (≤44 years old), female, urban, and low-income groups. However, the incidence was elevated only in the year of the thyroidectomies themselves in middle-aged and older, rural, and high-income groups. Conclusion: Patients with thyroid cancer who undergo thyroidectomy have depressive disorder more frequently than normal controls. However, the frequency of depressive disorder after thyroidectomy recovers in a shorter period in middle-aged or older, high-income, and rural-dwelling patients, compared to younger, low-income, and urban-dwelling patients.